Persistent Increase in Serum Alkaline Phosphatase in a Patient with Monoclonal Gammopathy of Undefined Significance - I. Ramasamy (Case Reports in Hematology)
We report the finding of alkaline phosphatase-immunoglobulin complex (macro-alkaline phosphatase (macro-ALP)) in a patient with persistently increased ALP activity. The identification of macro-ALP is important to rule out pathological causes of increased ALP activity and to avoid unnecessary diagnostic investigation. The patient was subsequently diagnosed with vitamin D deficiency, gallstone pancreatitis, and monoclonal gammopathy of undefined significance (MGUS). Macro-ALP can coexist with disease that can increase serum ALP activity. We report, for the first time, a case of macro-ALP in a patient with a monoclonal protein (M-protein).